Estimation of S-wave velocity profiles at Lima city, Peru using microtremor arrays - Quispe, Selene (2014)
Microtremor exploration was performed around seismic recording stations at five sites in Lima city, Peru in order to know the site amplification at these sites. The Spatial Autocorrelation (SPAC) method was applied to determine the observed phase velocity dispersion curve, which was subsequently inverted in order to estimate the 1-D S-wave velocity structure. From these results, the theoretical amplification factor was calculated to evaluate the site effect at each site. S-wave velocity profiles at alluvial gravel sites have S-wave velocities ranging from ∼500 to ∼1500 m/s which gradually increase with depth, while Vs profiles at sites located on fine alluvial material such as sand and silt have Swave velocities that vary between ∼200 and ∼500 m/s. The site responses of all Vs profiles show relatively high amplification levels at frequencies larger than 3 Hz. The average transfer function was calculated to make a comparison with values within the existing amplification map of Lima city. These calculations agreed with the proposed site amplification ranges.